Islamic Human Development Index (IHDI), institutional quality, macroeconomics and economic growth: empirical evidence from Organization of Islamic Cooperation (OIC) countries - Widiastuti, Tika; Hadi Ryandono, Muhammad Nafik; -, Siti Zulaikha; Al Mustofa, Muhammad Ubaidillah; Atiya, Nikmatul (2023)
This study examines the impact of the Islamic Human Development Index (IHDI), institutional quality, and macroeconomics on economic growth in 39 Organization of Islamic Cooperation (OIC). This study used a Randomized Effect Model and panel data from 2007 to 2019. The findings indicate that the Islamic Human Development Index (IHDI) as a proxy of human quality has a positive and significant impact on economic growth (1.225). Furthermore, institutional quality (0.994) and macroeconomics variables -population (0.926) and wage (0.034)- have a positive significant impact on economic growth. This study confirms that the IHDI, which comprehensively reflects human quality from a more Islamic perspective, encourage economic growth in OIC countries.